2019
DOI: 10.3390/ma12233856
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Photocathodic Protection Properties of ZnO/TiO2 Heterojunction Film Under Simulated Solar Light

Abstract: In this work, a novel double layer made of ZnO nanorod arrays and TiO2 nanorod arrays with anticorrosion function were successfully prepared on fluorine-doped tin oxide (FTO) substrate by a simple low-temperature solvothermal method. As compared with the pure TiO2 and pure ZnO film, the combination of the two films presented higher photocathodic protection performance for 316 stainless steel (316 SS) and Q235 carbon steel in 3.5 wt% NaCl solution. The composite film with ZnO nanoparticles layer between ZnO nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The solvothermal method, which employs an organic solvent instead of water, can also be employed to prepare high-purity heterojunction coatings with controlled particle size and morphology. , Guo et al produced NH 2 -MIL-125/TiO 2 heterojunction coatings through a solvothermal reaction at 150 °C for 20 h. 2-Aminoterephthalic acid was used as the raw material, and N , N -dimethylformamide and methanol were used as solvents (Figure C). TEM images demonstrated that a regular platelike NH 2 -MIL-125 was loaded onto the TiO 2 surface, with particle sizes ranging from 300 to 820 nm (Figure D).…”
Section: Synthesis Methods Of Tio2-based Heterojunction Coatingmentioning
confidence: 99%
“…The solvothermal method, which employs an organic solvent instead of water, can also be employed to prepare high-purity heterojunction coatings with controlled particle size and morphology. , Guo et al produced NH 2 -MIL-125/TiO 2 heterojunction coatings through a solvothermal reaction at 150 °C for 20 h. 2-Aminoterephthalic acid was used as the raw material, and N , N -dimethylformamide and methanol were used as solvents (Figure C). TEM images demonstrated that a regular platelike NH 2 -MIL-125 was loaded onto the TiO 2 surface, with particle sizes ranging from 300 to 820 nm (Figure D).…”
Section: Synthesis Methods Of Tio2-based Heterojunction Coatingmentioning
confidence: 99%
“…Furthermore, its high photogenerated carrier recombination rate diminishes its protection effect for metals in the dark state [18]. One of the most effective ways to overcome the above shortcomings is constructing heterojunction composites with other semiconductors that have narrow band gaps (such as BiVO 4 [19], WO 3 [20], ZnO [21] and ZnPc [22]).…”
Section: Introductionmentioning
confidence: 99%